Regulation of cancer progression by circRNA and functional proteins. Issue 1 (21st October 2021) - Chen, Junhong; Gu, Jie; Tang, Mengtian; Liao, Zhiqiang; Tang, Rui; Zhou, Lianqing; Su, Min; Jiang, Jiarui; Hu, Yingbin; Chen, Yongyi; Zhou, Yujuan; Liao, Qianjin; et al.
Abstract: Circular RNAs (circRNAs) are closed back‐splicing products of precursor mRNA in eukaryotes. Compared with linear mRNAs, circRNAs have a special structure and stable expression. A large number of studies have provided different regulatory mechanisms of circRNAs in tumors. Challenges exist in understanding the control of circRNAs because of their sequence overlap with linear mRNA. Here, we survey the most recent progress regarding the regulation of circRNA biogenesis by RNA‐binding proteins, one of the vital functional proteins. Furthermore, substantial circRNAs exert compelling biological roles by acting as protein sponges, by being translated themselves or regulating posttranslational modifications of proteins. This review will help further explore more types of functional proteins that interact with circRNA in cancer and reveal other unknown mechanisms of circRNA regulation. Abstract : (1) We highlighted a series of recently emerging studies of circular RNAs (circRNAs) and functional proteins regulating tumorigenesis and cancer progression. (2) RNA‐binding proteins (RBPs) modulate circRNA biogenesis in cancer. (3) CircRNA control posttranslational modification of proteins in cancer.